2021
DOI: 10.1371/journal.pone.0243675
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping identifies yellow rust resistance loci in Ethiopian durum wheat germplasm

Abstract: Durum wheat is an important cereal grown in Ethiopia, a country which is also its center for genetic diversity. Yellow (stripe) rust caused by Puccinia striiformis fsp tritici is one of the most devastating diseases threatening Ethiopian wheat production. To identify sources of genetic resistance and combat this pathogen, we conducted a genome wide association study of yellow rust resistance on 300 durum wheat accessions comprising 261 landraces and 39 cultivars. The accessions were evaluated for their field r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…26-105.61 Mbp in all the chromosomes, with an overall mean of 31.44 Mbp. This is much lower than the average physical distance (69.1 Mbp) for LD decay in Ethiopian durum wheat at the critical threshold of r 2 = 0.2 (Alemu et al, 2021). The marker distances at which the LD decayed across the older sub-genomes (A and B) were relatively lower than those for the D sub-genome, most likely because of the long evolutionary history of the A and B genomes as compared with the D genome.…”
Section: Discussionmentioning
confidence: 74%
“…26-105.61 Mbp in all the chromosomes, with an overall mean of 31.44 Mbp. This is much lower than the average physical distance (69.1 Mbp) for LD decay in Ethiopian durum wheat at the critical threshold of r 2 = 0.2 (Alemu et al, 2021). The marker distances at which the LD decayed across the older sub-genomes (A and B) were relatively lower than those for the D sub-genome, most likely because of the long evolutionary history of the A and B genomes as compared with the D genome.…”
Section: Discussionmentioning
confidence: 74%
“…GWAS studies, based on highthroughput genotyping tools, helped in defining genomic regions affecting such agronomic traits in landraces highlighting available superior alleles. Among others, the contribution to the yield of root system architecture traits and phenology were highlighted (Mengistu et al, 2016;Kidane et al, 2017a;Desiderio et al, 2019;Gupta et al, 2020;Alemu et al, 2021;A ́vila et al, 2021;Royo et al, 2021).…”
Section: Environmental Adaptation Traits From Durum Wheat Landracesmentioning
confidence: 99%
“…A number of wheat Yr genes including Yr15/YrH52/YrG303 8,31 , Yr24/Yr26 32 , Yr10 13 , YrC142 33 , YrAlp 34 , Yr64 35 , and Yr65 35 , have been previously mapped on chromosome arm 1BS. Many genomewide association studies have also shown marker-trait associations for stripe rust resistance on 1BS that could overlap with the positions of these Yr loci [36][37][38][39][40][41][42][43][44] . Of these genes, only Yr15/YrH52/YrG303 has been cloned as Wheat Tandem Kinase 1 (WTK1) and here we show that Yr84 localizes ∼86 Mb distal to WTK1, and that PI 487260 lacks Wtk1 based on genotyping with functional markers.…”
Section: Discussionmentioning
confidence: 99%